Essential and non-essential heavy metal levels in key organs of winter flounder (Pseudopleuronectes americanus) and their potential impact on body condition. (July 2021) - Foley, M.; Askin, N.; Belanger, M.P.; Wittnich, C.
Abstract: This study explored whether winter flounder, a benthic species, are potentially exposed to contaminants such as heavy metals released from the sediment of the Bay of Fundy/Gulf of Maine, both critical habitats identified to have increases in heavy metal levels. Experimentally in fish, exposure to certain heavy metals resulted in reduced weight for length and structural abnormalities, but it is unknown if this occurs in wild fish. Winter flounder (n = 72), harvested between 2015 and 2018 from the aforementioned western Atlantic region of Canada/USA, had detectable levels of most heavy metals, with some exhibiting levels of concern (arsenic, cadmium, lead, selenium, zinc) in muscle, liver, and kidney. A 1.4% incidence of structural abnormalities was noted. When compared to 1980 regionally matched flounder data, the 2018 flounder had significantly reduced weight for length, exacerbated with age. Clearly winter flounder are affected by worsening heavy metal contaminant levels in this geographic area. Highlights: Winter flounder had detectable levels of most heavy metals, some at levels of concern. Significant reductions in weight-for-length, exacerbated with age compared to 1980 1.4 incidence of structural abnormalities